Giant ganglioneuroma of the mediastinum: a case report - Song, Linfeng; Zhang, Jiaren; Tian, Binlin; Li, Yongzhe; Gu, Xiaoyu; Zhang, Youlun (Frontiers in Oncology, 2024)
Ganglioneuroma (GN) is a rare benign neurogenic tumor that originates from the sympathetic nerves. It is extremely uncommon to find a lesion originating from the mediastinum that occupies the entire left hemithorax. In this report, we present the case of a 48-year-old female patient with a large mediastinal GN who presented with cough, sputum, and wheezing. Multislice spiral-enhanced CT and magnetic resonance imaging (MRI) revealed a large oval mass in the left thoracic cavity. The surgical operation completely resected the lesion, and the histopathological examination of the resected specimen confirmed the diagnosis of giant ganglion cell neuroma of the mediastinum. Due to the low incidence of GN and the lack of specific imaging manifestations, many radiologists may lack sufficient knowledge of GN and may be prone to misdiagnosis, resulting in delayed treatment. To enhance radiologists’ awareness of giant ganglion cell neuroma of mediastinal origin occupying the thoracic cavity, we provided detailed CT/MRI imaging information for this case, along with a brief summary of similar previously reported cases, to highlight the specific clinical and radiological features of this condition.